Real world experience of brodalumab treatment in patients with moderate‐to‐severe plaque psoriasis in the Greek population: Results from an interim analysis of the BrIDGE study. Issue 12 (1st November 2022) - Rigopoulos, Dimitrios; Angelakopoulos, Charalampos; Apalla, Zoi; Georgiou, Sophia; Delli, Florentina; Drosos, Alexandros; Zafiriou, Efterpi; Katsantonis, John; Lazaridou, Elisavet; Panagakis, Pantelis; Papadavid, Evangelia; Papakonstantis, Markos; et al.
Abstract: Brodalumab's clinical efficacy and favorable safety profile have been demonstrated during controlled clinical trials, but real‐world data remain scarce. BrIDGE, an ongoing 104 week, observational, prospective, multicenter study conducted in Greece, enrolled moderate‐to‐severe plaque psoriasis patients, with body surface area (BSA) > 10 or psoriasis area severity index score (PASI) > 10 and dermatology life quality index (DLQI) > 10, based on European consensus, initiating brodalumab treatment as per routine clinical practice. This interim analysis includes evaluations 12–16 weeks following treatment initiation. Key efficacy endpoints included proportion of patients achieving static Physician's Global Assessment (sPGA) score of "clear/almost clear" (0/1) and a reduction ≥75%, 90%, 100% from baseline in PASI (PASI75, PASI90, and PASI100) at weeks 12–16. Other endpoints included time to achieve PASI100, changes in self‐reported DLQI and psoriasis symptom inventory (PSI) at weeks 12–16. From 200 patients (mean age 51.4 years, 70% male, mean disease duration 13.8 years) enrolled, 72.8% achieved sPGA of 0/1, whereas 70.2%, 47.5%, and 32.0% achieved corresponding PASI75, PASI90, and PASI100 responses following 12–16 weeks of brodalumab treatment, according to the "as‐observed" analysis. The mean time to achieve PASI100 was 13.7 ± 1.2 weeks for the 32% who achieved PASI100. Concurrent decreases in mean DLQI and PSI were observed. Furthermore, 90% adherence to brodalumab was noted and nine adverse events were reported. Brodalumab confers substantial clinical improvements short‐term as reflected by high levels of skin clearance in moderate‐to‐severe plaque psoriasis patients within 12–16 weeks of treatment under everyday clinical conditions, followed by improvements in symptoms and quality of life and a favorable safety profile.